2014
DOI: 10.1007/s11356-014-3578-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic interaction of Spirulina platensis and deltamethrin in freshwater fish Nile tilapia, Oreochromis niloticus: impact on lipid peroxidation and oxidative stress

Abstract: Spirulina platensis (SP) is one of the most commonly used dietary supplements in human and many animal species, including fish. Recently, it has gained more attention in fish not only for its growth-promoting and immunomodulatory effects but also for its antioxidant potential. The present study was conducted to investigate the protective role of two different dietary levels of SP on freshwater Nile tilapia; Oreochromis niloticus exposed to subacute deltamethrin (DLM) intoxication. Spirulina was supplemented at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(96 citation statements)
references
References 44 publications
6
90
0
Order By: Relevance
“…However, oversubstitution of fish meal with plant protein sources led to reduced growth performance, lower disease resistance, and the increased use of chemical drugs during aquaculture (Dossou et al, 2018;Sitjà-Bobadilla et al, 2005;Urán et al, 2008;Ye et al, 2019;Zhou, Chen, Ji, & Yu, 2017). Supplying an immunopotentiator, which could enhance the nonspecific defense mechanisms or the specific immune response of animals (Anderson, 1992), to plant protein-based diets has attracted research attention (Abdelkhalek, Ghazy, & Abdel-Daim, 2015;Awad & Awaad, 2017;Sahin et al, 2014;Zheng et al, 2017). To date, various extract preparations from plants and other animals have been used as immunopotentiators in aquaculture (Dawood, Koshio, & Esteban, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, oversubstitution of fish meal with plant protein sources led to reduced growth performance, lower disease resistance, and the increased use of chemical drugs during aquaculture (Dossou et al, 2018;Sitjà-Bobadilla et al, 2005;Urán et al, 2008;Ye et al, 2019;Zhou, Chen, Ji, & Yu, 2017). Supplying an immunopotentiator, which could enhance the nonspecific defense mechanisms or the specific immune response of animals (Anderson, 1992), to plant protein-based diets has attracted research attention (Abdelkhalek, Ghazy, & Abdel-Daim, 2015;Awad & Awaad, 2017;Sahin et al, 2014;Zheng et al, 2017). To date, various extract preparations from plants and other animals have been used as immunopotentiators in aquaculture (Dawood, Koshio, & Esteban, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Under normal homeostasis, the cells maintain the ROS levels with endogenous nonenzymatic and enzymatic-antioxidants. [10][11][12] The risk of cell injury may also be prevented by natural antioxidants including dietary polyphenols. Dietary polyphenolic compounds have received a great deal of attention because of their beneficial effects on health, including protection against oxidative stress and degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Research Mutlu, Aydin, and Kutlu (2015) reported that the total protein and albumin Nile tilapia, O. niloticus decreases because exposed to copper sulfate, fish that are exposed to subacute intoxication deltamethrin also showed a decrease in total protein and albumin (Abdelkhalek, Ghazy, & Abdel-Daim, 2015).…”
Section: Biochemical Parameters Findings In Blood Serummentioning
confidence: 99%